Effect of DIC Spatial Resolution, Noise and Interpolation Error on Identification Results with the VFM. (24th March 2015) - Rossi, M.; Lava, P.; Pierron, F.; Debruyne, D.; Sasso, M.
Abstract The use of experimental tests that involve full‐field measurements to characterize mechanical material properties is becoming more widespread within the engineering community. In particular digital image correlation (DIC) on white light speckles is one of the most used tools, thanks to the relatively low cost of the equipment and the availability of dedicated software. Nonetheless the impact of measurement errors on the identified parameters is still not completely understood. To this purpose, in this paper, a simulator able to numerically simulate an experimental test, which involves DIC is presented. The chosen test is the Unnotched Iosipescu test used to identify the orthotropic elastic parameters of composites. Synthetic images are generated and then analysed by DIC. Eventually the obtained strain maps are used to identify the elastic parameters with the Virtual Fields Method (VFM). The numerical errors propagating through the simulation procedure are carefully characterized. Besides, the simulator is used to compare the performances of DIC and the grid method in the identification process with the VFM. Finally, the influence of DIC settings on the identification error is studied as a function of the camera digital noise level, in order to find the best testing configuration.